1968
DOI: 10.1021/ac60263a020
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of a sulfide ion-selective membrane electrode in alkaline solution

Abstract: Log Q = 2.74 -2.78 Ec, 0.55 > Ec > 0 (4) where Q is the amount of copper deposited in microcoulombs (/uC). The total quantity of copper deposited at 0 V, Q*, is 540 ± 25 pC/cm2 for a reduced or an oxidized electrode. Q* represents the total copper involved in the surface controlled reductions and oxidations, Ri -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(36 citation statements)
references
References 11 publications
6
30
0
Order By: Relevance
“…The flameless atomic absorption (AA) technique has a limit of detection of about 3 pg Cu in aqueous solution (1).…”
Section: Lawrence L Edwards' and Beniamino Oregioni International Lamentioning
confidence: 99%
“…The flameless atomic absorption (AA) technique has a limit of detection of about 3 pg Cu in aqueous solution (1).…”
Section: Lawrence L Edwards' and Beniamino Oregioni International Lamentioning
confidence: 99%
“…Silver sulfide selective membrane electrodes were developed in the twentieth century (Hseu and Rechnitz 1968). Silver sulfide selective membrane electrodes were developed in the twentieth century (Hseu and Rechnitz 1968).…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…The selectivity of a commercial sulfide ion-selective electrode has been reported to be in the same range of sulfide ion concentration as obtained in this study; however better slope of -30 mV is reported. 9 Response of the bromide selective membrane to sulfide ion was checked and a typical result is shown in Fig. 3.…”
Section: Response To Br -And S 2-ionsmentioning
confidence: 99%